Blended Learning: Analysis of University Student Learning Motivation for Citizenship Learning Courses in Elementary Teacher Education - Latif, Ardiyan; Jabar, Cepi Safruddin Abdul; Mustadi, Ali; Wijayanti, Inggit Dyaning (AL-ISHLAH: Jurnal Pendidikan, 2024)
The COVID-19 pandemic highlighted the need for ongoing education, prompting the education sector to seek alternatives to solely online learning. One of the steps that this university has taken is to combine the benefits of face-to-face and online learning through the use of technology, which is called blended learning. This study aims to assess the extent of student motivation for learning in a mixed learning environment in the Citizenship Learning course within the Elementary School Teacher Education department at UIN Sunan Kalijaga, Yogyakarta. This study employs a mixed method approach, with a sample size of 30 students as participants. Data for the study was acquired via observations, interviews, and questionnaires. The study results showed that the level of university student motivation towards Citizenship Learning through blended learning was 63.72% with a high category. This study showed that students’ learning motivation remains strong when using blended learning despite challenges like internet network reliability, device availability, and implementing appropriate learning methodologies.